PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Frederich Soflanputra Sakir, 06.25.02.0035; Suko Priyono, Bambang (Students Journal of Economic and Management, 2013)
This study aims to describe and analyze the effect of work motivation and work discipline to the performanceof an employee working at the Department of Industry, Trade and Cooperatives (DISPERINDAGKOP)Manggarai - NTT. The formulation of the problem in this research is How does influence work motivationand work discipline on employee performance DISPERINDAGKOP Manggarai. Data collection methodsused in this research is by using questionnaires by spreading a list of questions to respondents in order toobtain information. The data collected was analyzed using data analysis methods used in this research thatTest Validity, Reliability, Multiple Linear Regression, Test of Determination (R2), F test and t-test. Based onthe analysis it can be concluded that: 1) There is a positive and significant relationship between WorkMotivation on Employee Performance. 2) There is a positive and significant relationship between Workdiscipline and 3) Testing together using F test showed that motivation and discipline work together to have asignificant effect on performance.Key word : Work motivation, Work discipline and employee Performance